Can we predict poor prognosis in Fournier gangrene? - Özlülerden, Yusuf; Başer, Aykut; Çelen, Sinan; Alkış, Okan (Journal of Surgery and Medicine, 2020)
Aim: Fournier’s gangrene (FG) is a rapidly progressing and highly mortal necrotizing fasciitis that develops due to polymicrobial infection of the genital, perineal and perianal regions. Advanced age, comorbidities, width of the infected area, leukocyte-lymphocyte ratio, number of debridement performed, and Fournier’s gangrene severity index (FGSI) score are reported as prognostic factors for FG. In our study, we aimed to present the clinical and laboratory findings that can be used to predict poor prognosis in Fournier gangrene. Methods: In this retrospective cohort study, the files of 83 patients treated for FG were retrospectively analyzed. Demographic data, laboratory findings, treatments, age adjusted Charlson comorbidity index (ACCI), FGSI score, LRINEC score, complications and mortality were noted. Risk factors affecting mortality were determined. Results: Male/female ratio was 7.3. The mean age of the patients were 55.4 years. The mortality rate was 21.7%. The mean ACCI scores (Mortality group: 6.00 (2.72), survivors’ group: 2.66 (2.39)) and FGSI scores (Mortality group; 11.22 (3.2), survivors’ group; 3.25 (2.08)) of non-surviving patients were higher than those of survivors (P<0.001, P<0.001, respectively). Also, the mean neutrophil-lymphocyte ratio (Mortality group: 21.05 (15.67), survivors’ group: 11.62 (10.50), (P=0.013), and the mean LRINEC score (Mortality group: 7.17 (2.03), survivors’ group: 3.18 (2.59)) (P=0.001) were higher among non-survivors. Cut off values for FGSI score, LRINEC, ACCI, and neutrophil / lymphocyte ratio were 7.5 (94.4% sensitivity and 95.4% specificity), 4.5 (94.4% sensitivity and 67.7% specificity), 3.5 (77.8% sensitivity and 73.8% specificity), and 8.70 (72.2% sensitivity and 52.3% specificity), respectively, in predicting mortality. Mortality was higher in female patients compared to males (P=0.02), and among the diabetics (P=0.05). Conclusion: We think that risk factors such as advanced age, diabetes, female gender, high ACCI score, high FGSI scores, high LRINEC scores and high neutrophil lymphocyte ratio are predictive of poor prognosis in FG.